A Mediterranean record of Eulalia ornata (Annelida: Phyllodocidae) corroborating its fidelity link with the Sabellaria alveolata-reef habitat - Schimmenti, E.; Musco, L.; Lo Brutto, S.; Mikac, B.; Nygren, A.; Badalamenti, F. (Mediterranean Marine Science, 2015)
Among marine habitats Sabellaria alveolata -reefs deserve protection since they provide important ecosystem services and positive effects on biodiversity. Several marine species are listed among the S. alveolata -reef associated fauna, but characteristic species were seldom reported. Eulalia ornata (Annelida, Phyllodocidae) might represent an exception, since it appears common/abundant in S. alveolata -reefs of the Eastern Atlantic. The most evident geographical mismatch in the distributions of E. ornata and these biogenic reefs occurs in the Mediterranean Sea, where S. alveolata -reefs are commonly found, but E. ornata was never recorded, whilst E. viridis , a non-Mediterranean species, was previously listed among the dominant reef-associated taxa. The faunal characterization of the sabellarid reefs along the Sicily Channel revealed an Eulalia species as the dominant taxon associated with that habitat in the area. A taxonomic approach integrated with DNA barcoding, and comparisons with closely related species, allow us to report E. ornata as a new record for the Mediterranean Sea. We describe patterns of abundance and distribution and corroborate its status as a preferential species in the S. alveolata -reef habitat. Focusing on the biology and ecology of E. ornata could help us to better understand the dynamics and functioning of this valuable European shallow marine habitat.
World Polychaeta Database (WPolyDb)